A biomechanical model of feeding kinematics for Dunkleosteus terrelli (Arthrodira, Placodermi). Issue 2 (8th April 2009) - Anderson, Philip S. L.; Westneat, Mark W.
Abstract : Biomechanical models illustrate how the principles of physics and physiology determine function in organisms, allowing ecological inferences and functional predictions to be based on morphology. Dynamic lever and linkage models of the mechanisms of the jaw and skull during feeding in fishes predict function from morphology and have been used to compare the feeding biomechanics of diverse fish groups, including fossil taxa, and to test ideas in ecological morphology. Here we perform detailed computational modeling of the four-bar linkage mechanism in the skull and jaw systems of Dunkleosteus terrelli, using software that accepts landmark morphological data to simulate the movements and mechanics of the skull and jaws during prey capture. The linkage system is based on the quadrate and cranio-thoracic joints: Cranial elevation around the cranio-thoracic joint forces the quadrate joint forward, which, coupled with a jaw depressor muscle connecting the jaw to the thoracic shield, causes the jaw to rotate downward during skull expansion. Results show a high speed transmission for jaw opening, producing a rapid expansion phase similar to that in modern fishes that use suction during prey capture. During jaw closing, the model computes jaw and skull rotation and a series of mechanical metrics including effective mechanical advantage of the jaw lever and kinematic transmission of the skull linkage system. Estimates of muscle cross-sectional area based on the largest of five specimens analyzed allow the bite force and strike speed to be estimated. Jaw-closing muscles of Dunkleosteus powered an extraordinarily strong bite, with an estimated maximal bite force of over 6000 N at the jaw tip and more than 7400 N at the rear dental plates, for a large individual (10 m total length). This bite force capability is among the most powerful bites in animals. The combination of rapid gape expansion and powerful bite meant that Dunkleosteus terrelli could both catch elusive prey and penetrate protective armor, allowing this apex predator to potentially eat anything in its ecosystem, including other placoderms.